Learning Innovation Combination of Project Based Learning and Problem Based Learning Based on Research and Devotion - Nursalam Nursalam; Suardi Suardi (Universitas of Muhammadiyah Makassar, 2024)
The main problem in this research is learning innovation in the lecture process which can improve students' collaborative, creativity, communication and critical thinking abilities. The aim of this research is to improve students' collaborative, creative, communication and critical thinking abilities through a combination of project based learning (PJBL) and problem based learning (PBL) based on research and devotion. This research uses mixed research methods. Research informants, qualitative research using purposive sampling amounted to 2 people, while determining the research sample used a total sampling technique of 50 respondents. The data collection techniques used were questionnaires, observation, interviews and documentation. Qualitative data analysis was carried out through the stages of data reduction, data display and drawing conclusions, while quantitative data analysis used questionnaire verification, tabulation of questionnaire data and percentage of questionnaire data. The validity of qualitative data uses source triangulation and method triangulation, while quantitative data uses reliability tests (accuracy) and validity tests (correctness). The results of the research show that the application of a combination of research and devotion-based project based learning (PJBL) and problem based learning (PBL) in the Sociology and Anthropology of Education courses has increased students' collaboration, creativity, communication and critical thinking abilities